Automated Digital Image Optimisation in Intraoperative 2D and 3D Imaging Using a Mobile C-Arm With Flat-Panel Detector - Groh, Johannes; Perl, Markus; Bräuer, Lars; Stadthalter, Holger (International Journal of Medical Robotics and Computer Assisted Surgery, 2025)
Background: Assistance tools for intraoperative 2D and 3D imaging to decrease acquisition effort and to improve assessment of 3D image data were evaluated. Methods: Two automated optimisation procedures were evaluated in a cadaver (Cios Spin, Siemens, Germany): The ScrewScout function for assisted pedicle screw assessment. Then, an algorithm for metal artefact reduction (MAR). Additionally, a tool for simplified setting of image contrast and brightness was evaluated regarding the result and elapsed time. Results: The time required without automated assistance was 83s [70–105]. With the computer assistance, this time was significantly lower at 22s [15–32] (p = 0.003). MAR resulted in an improvement in image impression. This improvement became smaller with increasing clinical experience. The time needed for setting of image acquisition parameters was significantly (p = 0.05) lowered from 140s [24–389] to 61s [14–166] using the assistance tool. Conclusions: Automated assistance tools for image optimisation can provide practical support in the intraoperative setting.
CRIS-Team Scopus Importer:2025-03-14
Keywords: automated image analysis; intraoperative imaging; MAR; metal artifact reduction; ScrewScout; SpotAdapt